Outcomes of extracorporeal membrane oxygenation cannulation strategy in lung transplantation: A retrospective cohort study - Jiayang Li; Bu Long; Wenjie Xie; Yaoliang Zhang; Chao Yang; Mengyang Liu; Xin Xu; Lan Lan (Asian Journal of Surgery)
Objectives: Extracorporeal membrane oxygenation (ECMO) with different cannulation strategies is determined according to surgical position and patient condition. However, no cannulation guidelines have been proposed. This retrospective study assessed the outcomes of diverse ECMO cannulation strategies in patients undergoing lung transplantation (LTx). Methods: Data of patients undergoing intraoperative veno-arterial ECMO-assisted LTx were retrospectively collected from December 1st, 2015 to October 31st, 2021. Patients were classified into three groups based on the different cannulation strategies: femoral artery-femoral vein (F–F)-ECMO, axillary artery-femoral vein (A-F)-ECMO, and ascending aorta-femoral vein (AAO-F)-ECMO. The F-F-ECMO, A-F-ECMO, and AAO-F-ECMO groups comprised 34, 44, and 30 patients, respectively. Main results: The AAO-F-ECMO group exhibited a significantly shorter duration of postoperative ECMO therapy (3 vs. 2 vs. 0 days, P < 0.01).the level of postoperative proBNP was lower on the third and seventh days (P < 0.001). AAO-F-ECMO patients had a significantly lower incidence of postoperative infections, heart failure, and bleeding (P < 0.05). Similar outcomes were observed in postoperative survival rates among the three groups (P > 0.05). Conclusions: Ascending aorta-femoral vein ECMO can provide sufficient and effective aerobic blood to perfuse organs with fewer side effects than cannulation in the femoral artery-femoral vein or axillary artery-femoral vein.